Perwalian Menurut Para Fuqaha (Tela'ah Kitab Fiqih Islam Wa Adillatuh, Dan Kitabun Nikah Syekh Muhammad Arsyad Al-Banjari) - Muhammad Parhan, Fathullah; Abdul Hamid; Lutfi Annisa (Sharia Journal and Education Center Publishing, 2024)
Abstract This study examines the rights, conditions, and order of marriage guardianship according to the Imams of the schools of thought and jurists, with a review of the books